Engendering Rome : women in Latin epic - Keith, Alison (Roman literature and its contexts., 2000)
Heroism has long been recognised by readers and critics of Roman epic as a central theme of the genre from Virgil and Ovid to Lucan and Statius. However the crucial role female characters play in the constitution and negotiation of the heroism on display in epic has received scant attention in the critical literature. This study represents an attempt to restore female characters to visibility in Roman epic and to examine the discursive operations that effect their marginalisation within both the genre and the critical tradition it has given rise to. The five chapters can be read either as self-contained essays or as a cumulative exploration of the gender dynamics of the Roman epic tradition. The issues addressed are of interest not just to classicists but also to students of gender studies.